Effects of peripheral cooling on characteristics of local muscle - Drinkwater, E. (Thermoregulation and human performance. Physiological and biological aspects, 2008)
hile humans maintain body core temperature within a strict homeostatic range, skin and peripheral muscle temperature may experience a wide temperature variation. Much of the literature investigating cooling on human performance involves cooling of the core, though many performance effects relate to cooling of the periphery. No standard method exits to investigate the effects of cooling, so protocols range across a variety of temperatures (10-42°C), temperature assessment methods (skin, intramuscular), cooling mediums (air, water immersion), muscle fibre type (species, fast or slow twitch), contraction type (evoked or voluntary, isometric or dynamic), and isolated versus intact fibres. Despite these variables, there is general agreement that rate properties are slowed with almost any level of cooling thereby most substantially reducing muscle power. The slowed enzymatic processes and slowed nerve conduction that impair rate of force development also likely reduce local muscular endurance during dynamic contractions and impair manual dexterity ( 35 C). Both the voluntary and evoked force development capacities of muscle is unimpaired until cooling is quite severe (<27°C). While most of these effects occur independently of central activation, purposeful core cooling for the purpose of improving athletic performance should be used cautiously to avoid the deleterious effects of peripheral cooling.